Chomp-o-rama : the strange ways that animals eat - Birmingham, Maria (Owlkids Books, 2025)
"Lively text and vibrant, humorous illustrations present twelve food-focused scenarios in this inventive, engaging, and surprisingly relatable introduction to animal behavior. After a brief introduction, twelve playful comparisons demonstrate ways a variety of animals and humans are the same but different when it comes to their snacks and meals. The animals are from a wide range of geographic habitats, from arctic foxes to Amazonian turtles and butterflies to Canada Jays. And the kids we see are culturally diverse. On the recto, a human activity is described with a single sentence. With a turn of the page, the recto reveals the animal comparison along with a short factual paragraph explaining the animal's behavior. The final page offers a brief explanation of why humans and animals need to eat: nutritious food gives your body the energy to think, move, and grow. It goes on to explain that different animals have different food needs and introduces the terms herbivore, carnivore, and omnivore. Includes a list of suggested reading as end matter."--